Teaching Hands-Only CPR in Schools: A Program Evaluation in San José, Costa Rica - Kristin M. Schmid; Raquel Quiros García; Manrique Montoya Fernandez; Nee-Kofi; Steven R. Lowenstein (Ubiquity Press, 2018)
Background: Hands-only bystander CPR increases survival from out-of-hospital cardiac arrest. Video-based CPR instruction in schools has been proposed as a means to mass-educate laypersons in Hands-only CPR™ (HOCPR), in developed as well as developing countries. Objectives: The purpose of this study is to determine whether a brief video- and mannequin-based instructional program, developed by the American Heart Association (AHA), is an effective strategy for teaching Costa Rican middle- and high-school age children to learn the steps of HOCPR. Methods: This study took place in four educational centers that spanned the entire socioeconomic spectrum within the Grand Metropolitan Area of Costa Rica. Three hundred and eight students from the sixth to eleventh grades participated. The intervention included exposure to the AHA "CPR Anytime" video and practice with CPR mannequins. Before and after the intervention, students took a four-question, multiple-choice quiz that measured their knowledge of the correct steps and proper techniques of HOCPR; a separate question assessed their level of comfort "doing CPR on someone with a cardiac arrest." Pre- and post-intervention "percent correct" scores were compared and tested for statistical significance using paired t-tests or the McNemar test as appropriate. Improvement in knowledge and comfort levels were also compared across the different educational centers and compared with similar programs implemented in the United States. Results: The students' overall scores (mean percent correct) on the multiple choice questions more than doubled after training (40.9% ± 1.4% before training vs. 92.5% ± 0.9% after training, p < 0.00001). Improvements were observed in each school, regardless of geographic location or socioeconomic status. Knowledge of the appropriate steps of HOCPR doubled after training (42.2% before training vs. 92.5% after training, p < 0.000001). Post-intervention, a majority (73%) of children reported comfort with performing CPR on an individual who had suffered a cardiac arrest. Conclusion: This study demonstrates the effectiveness of the AHA "CPR Anytime" program in teaching HOCPR to school-age children within the Grand Metropolitan Area of Costa Rica. Additional studies are needed to measure longer-term knowledge retention and students' ability to perform CPR in simulated cardiac arrest settings.